Cranky Games through Peaceful Values on Improving Early Adolescent Mental Health in Banyuwangi Regency: Cranky Games through Peaceful Values on Improving Early Adolescent Mental Health in Banyuwangi Regency - Fajar Wahyu Prasetyo -; Agus Mursidi (SOSIOEDUKASI, 2023)
This article aims to describe the development of peace cranks towards improving early adolescent mental health in Banyuwangi Regency. The research design uses a literature review through descriptive analysis which is described regularly. To develop further research, researchers used this type of R&D research which was carried out in 5 stages. Research and development procedures are carried out starting from the stages of problem identification, data collection, product design, product validation, and finally, product revision. Product evaluation is carried out by material experts, media experts and practitioner experts. Meanwhile, product trials were carried out on students in groups of 8-12 students in their early teens. The types of data obtained and used are qualitative and quantitative data. Data collection uses a mental health scale, material expert scale, media expert scale and practitioner expert scale. Data analysis using qualitative and quantitative analysis. The whole discussion is described in this article